POLA ASUH DEMOKRATIS UNTUK MENGEMBANGKAN PERILAKU ALTRUISME ANAK DI ERA GLOBAL - Novita Angraeni; Sely Sisca Andriani; Shinta Muliawati; Charis Faozi (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
Globalization has a negative impact, one of which is for the social development of children. While humans basically can not live alone but need the help of others and help each other. Altruism is a voluntary action by a person or group of people to help others without expecting a refund. Democratic parenting plays an important role in the formation of the child's behavior and personality, which cares and respects the freedom of the child. Democratic parenting supports the development of positive emotions and empathy that are closely related to the development of child altruism behavior.